Patients' Experiences With Illness, Treatment, and Decision-Making for Esophageal Cancer: A Qualitative Study in a Danish Hospital Setting - Malene Kaas Larsen; Helen Schultz; Michael Bau Mortensen; Regner Birkelund (SAGE Publishing, 2020)
Patients with curable esophageal cancer or cancer in the esophageal junction face several challenges during the course of their treatment because of the burden of uncertainty in their prognoses and complexity and side effects of the treatment. The aim of this study is to explore patient experiences with illness, treatment, and decision-making in the context of esophageal cancer. A qualitative approach using phenomenological-hermeneutical methodology was used. Data consisted of participant observations and interviews. We analyzed the data based on Ricoeur's theory of interpretation. The results show that patients with esophageal cancer are putting their ordinary lives on hold and experiencing the meal as a battleground during treatment. Patients strive to maintain autonomy, gain control, and take ownership. The results emphasize the need for a systematic approach to establish an ongoing dialogue with patients throughout the course of treatment.